Assessing the State of the Pelagic Habitat: A Case Study of Plankton and Its Environment in the Western Irish Sea - Scherer, Cordula; Gowen, Richard J.; Tett, Paul (Frontiers in Marine Science, 2016)
Much work had been undertaken on tracking change in the condition of marine pelagic ecosystems and on identifying regime shifts. However, it is also necessary to relate change to states of good ecosystem health or what the European Marine Strategy Framework Directive (MSFD) calls 'Good Environmental Status' (GES). Drawing on existing scientific and legislative principles, including those of OSPAR's 'Strategy to Combat Eutrophication', we propose a framework for assessing the status of what the MSFD calls the 'pelagic habitat' in temperate coastal seas. The framework uses knowledge of local ecohydrodynamic conditions, especially those relating to the stratification and optical environment, to guide expectations of what would be recognised as healthy in terms of ecosystem 'organisation' and 'vigour'. We apply this framework to the seasonally stratified regime of the Western Irish Sea, drawing on published and new work on stratification, nutrient and phytoplankton seasonal cycles, zooplankton, and the implications of plankton community structure and production for higher trophic levels. We conclude that, despite human pressures including nutrient enrichment, and the food-web effects of fisheries, the pelagic ecosystem here is in GES, and hence may be used as a reference for the 'Plankton Index' method of tracking change in state space in seasonally stratified waters.